3D profilometry for turbine blade shape profiling - Chng, Sian Shing. (2010)
The rising need for fast and accurate 3D profile measurements has been a concern over the years. There is an increase in popularity for 3D profile measurement by optical technique known as ''Fringe Projection Profilometry''. It allows for fast 3D profile measurement with totally no contact with the measuring object. The Compact Fringe Projection Profilometer is designed to carry out 3D profile measurement on engineering components such as turbine blades conveniently. It consists of a CCD camera and a digital light projector as the measuring apparatus which are connected to a personal computer. The camera and projector will take command through the interface of the software known as ''Fringe''. This profilometer will require two types of calibrations known as ''Out of Plane Calibration'' and ''Camera Calibration''. A comparison is to be made between the Compact Fringe Projection Profilometer and Laser Displacement Sensor System in term of factors such as measuring time, repeatability, measurement range and setup cost.